2018
DOI: 10.32828/mdj.v14i1.753
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental anxiety in relation to sociodemographic factors using two psychometric scales in Baghdad

Abstract: Background: In spite of advances in dentistry, anxiety about dental treatment and thefear of pain remains public health problem and is a significant impediment todental treatment. The purpose of this study was to assess the levels of dentalanxiety in patients who referred to Al-Mustansiriyah dental clinics and Al-ShiekhOmar specialized dental center in Baghdad and their relation to their gender, age,educational level.Materials and methods: The study was done on (800) patients, aged (20-59) years inBaghdad. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…Age: We found that age had not have a significant relationship with dental anxiety which is in agreement with Wong and Reed Lytle [3], Rankin and Haris [26] and Arslan, et al [27]. In contrast, several studies have shown that younger patients are more anxious than older ones [11,20,28,29]. More specifically, Hamissi, et al [7] reported a significant relation between dental anxiety and age in Persian patients.…”
Section: What Are the Probable Factors Affecting Patient's Dental Anxiety (Stai-s)? (Which Have Searched In This Study)supporting
confidence: 88%
“…Age: We found that age had not have a significant relationship with dental anxiety which is in agreement with Wong and Reed Lytle [3], Rankin and Haris [26] and Arslan, et al [27]. In contrast, several studies have shown that younger patients are more anxious than older ones [11,20,28,29]. More specifically, Hamissi, et al [7] reported a significant relation between dental anxiety and age in Persian patients.…”
Section: What Are the Probable Factors Affecting Patient's Dental Anxiety (Stai-s)? (Which Have Searched In This Study)supporting
confidence: 88%
“…According to the results of the present study, there was a significant difference among the three groups of elementary education, high school, and university degrees in terms of mean dental anxiety. In this regard, subjects with primary education experienced a higher level of anxiety, compared to the other two groups, which is congruent with the results obtained by Saeed, Saatchi, et al, and Firat [43][44][45] . According to these studies, the level of dental anxiety decreased with increased literacy level.…”
Section: Discussionsupporting
confidence: 91%
“…The percentage reductions in BP were higher in males than in females at all visits but are not statistically significant, and this result agrees with Huang et al in 2017 6. This may be linked to the fact that females had greater average levels of anxiety than males 17,18. Therefore, the decreasing anxiety in males leads to activation of the PNS, which leads to a decrease in BP in males that is higher than that in females.…”
Section: Discussionsupporting
confidence: 86%
“…We chose patients whose ages ranged from 20–65 years because these ages represent the ages at which most patients undergo root canal treatment for maintaining their teeth. The 51–65 age group constituted 47% of the total sample, and this may be related to the fact that younger patients may have less time to go to endodontists and maintain their teeth; additionally, financial factors may form a barrier that prevents them from making endodontic visits, or it may be related to dental or endodontic anxiety 15–18…”
Section: Discussionmentioning
confidence: 99%